Electronic Communication and Changing Organizational Forms - Fulk, Janet; DeSanctis, Gerardine (Organization Science, 1995)
We introduce this Special Issue by providing an overview of the interplay between communication technology and various dimensions of new organizational forms. We consider the major factors motivating dramatic change within and between organizations today, and describe key dimensions of intraorganizational and interorganizational forms that are linked to electronic communication technologies: vertical control, horizontal coordination, size of organization and constituent units, new types of coupling, core product, communication cultures, ownership and control, interorganizational coupling, strategic alliances, and interstitial linking. Our purpose is to sample the changes attendant upon advances in electronic communication and organizational forms, with the goal of energizing future research. Our overview uncovers possibilities for new avenues of study within the technology-organization relationship and reveals the important contributions made by the articles in this Special Issue.